Drug Therapy Problems and Factors Affecting Drug Therapy Problems of Patients with Chronic Non-Communicable Diseases at Bueng Kan Hospital in Bueng Kan Province - Phanthana, Sirawich (Journal of Preventive Medicine Association of Thailand, 2022)
This Cross-sectional descriptive study aimed 1) to study drug therapy problems of patients with chronic non-communicable diseases at Bueng Kan Hospital in Bueng Kan and 2) to analyze factors affecting drug therapy problems of patients with chronic non-communicable diseases. The sample was 420 people using Convenience Sampling from patients with chronic non-communicable diseases at Bueng Kan Hospital in Bueng Kan between 4 October 2021 to 30 December 2021. Data was collected using a questionnaire and analyzed using descriptive statistics such as percentage, mean, and standard deviation. The relationship between independent variables and dependent variables was analyzed using Logistic Regression Analysis. The findings revealed that 1) Drug therapy problems in patients with chronic non-communicable diseases can be classified into three categories: overdosing, underdosing, and inconsistent drug use. 122 patients, or a quarter of all patients, had drug therapy problems. The prevalence of drug therapy problems of NCDs was 29.05 percent. Most of them took fewer medications than prescribed by their doctor. 2) Univariate analysis results into Multivariate analysis, it can be concluded that there were 5 factors related to the drug therapy problems of patients with chronic non-communicable diseases as follows: 2.1) The main factors for personal characteristics are age and income, 2.2) The main factor in medicine use is medicine list, 2.3) The main factor in the knowledge of drug use is knowledge of medicinal properties, 2.4) The main factors for attitudes about drug use are attitudes about its medicinal properties and; 2.5) The supportive factors for family support include the provision of medicines, food, and facilities for the patient. In conclusion, to prevent drug therapy problems of patients with chronic non-communicable diseases, the policy to enhance knowledge, correct attitudes about drug use among patients, and focus more on promoting activities among 51 years old up patients should be emphasized. For example, building a health care network among the elderly, building a good relationship between the patient and the family, as well as developing a function to recommend the use of various medications in an application that the patient can conveniently use on their personal mobile phone.